Entrepreneurial patent management in pharmaceutical startups. Issue 7 (July 2016) - Holgersson, Marcus; Phan, Tai; Hedner, Thomas
Highlights: Patenting is crucial for success in the pharmaceutical industry. We explore patent management in pharmaceutical startups. Startups encounter several challenges when managing patenting. Resource constraints require adapted strategies in startups. We provide several strategies to strengthen and extend patent protection. Abstract : Startups fill an increasingly important role as innovators in the pharmaceutical industry, and patenting is typically central to their success. This article aims to explore patent management in pharmaceutical startups. The results show that startups need to deal with several challenges related to patenting and an 'entrepreneurial' approach to patent management is called for. Resource constraints, venture capital provision, exits and other conditions and events must be readily considered in the patent management process to build a successful pharmaceutical venture, something that could benefit the pharmaceutical industry as a whole.